hedgehog and wing development in Drosophila: a morphogen at work? - Vervoort, M. (BioEssays, 2000)
In Drosophila, Hedgehog (Hh) is a key regulator of limb development and activates decapentaplegic (dpp), a gene encoding a TGFbeta-related factor that controls growth and patterning of the limbs. During wing development, Hh also has morphogen-like Dpp-independent functions, controlling the morphogenesis of the central part of the wing through the activation of the evolutionarily conserved transcription factors encoded by the iroquois and collier genes. The ways in which Hh forms an activity gradient to lay the basis of patterning of the adult wing are described here. As the signal transduction pathway of Hh is strongly conserved during evolution and human Hh may be implicated in congenital diseases and cancers, these observations provide important advances which may help in understanding the function of Hh proteins in normal and pathological development and tumourigenesis in humans.